2014
DOI: 10.1155/2014/418458
|View full text |Cite
|
Sign up to set email alerts
|

DBC1/CCAR2 and CCAR1 Are Largely Disordered Proteins that Have Evolved from One Common Ancestor

Abstract: Deleted in breast cancer 1 (DBC1, CCAR2, KIAA1967) is a large, predominantly nuclear, multidomain protein that modulates gene expression by inhibiting several epigenetic modifiers, including the deacetylases SIRT1 and HDAC3, and the methyltransferase SUV39H1. DBC1 shares many highly conserved protein domains with its paralog cell cycle and apoptosis regulator 1 (CCAR1, CARP-1). In this study, we examined the full-length sequential and structural properties of DBC1 and CCAR1 from multiple species and correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 96 publications
0
27
0
Order By: Relevance
“…Also, enhancing sir‐2.1 activity through caloric restriction enhances the transcription of hsp‐70 (Raynes, Leckey, Nguyen, & Westerheide, 2012). Although C. elegans does not possess a known ortholog to AROS, CCAR2 does have a worm ortholog named CCAR‐1, previously called LST‐3 (Brunquell, Yuan, Erwin, Westerheide, & Xue, 2014). We were therefore interested in determining whether negative regulation of the HSR by the SIRT1 modulator CCAR2 also occurs in the worm, and how this interaction would impact stress‐related responses and longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Also, enhancing sir‐2.1 activity through caloric restriction enhances the transcription of hsp‐70 (Raynes, Leckey, Nguyen, & Westerheide, 2012). Although C. elegans does not possess a known ortholog to AROS, CCAR2 does have a worm ortholog named CCAR‐1, previously called LST‐3 (Brunquell, Yuan, Erwin, Westerheide, & Xue, 2014). We were therefore interested in determining whether negative regulation of the HSR by the SIRT1 modulator CCAR2 also occurs in the worm, and how this interaction would impact stress‐related responses and longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Through different protein-protein interactions, CCAR1 can activate multiple downstream targets implicated in proliferation, apoptosis and differentiation (Kim et al, 2008;Lu et al, 2012;Ou et al, 2009). CCAR1 possesses a DNAbinding domain, a RNA-binding domain and several protein interaction domains, indicating that CCAR1 might participate in multiple processes (Brunquell et al, 2014). However, functions of CCAR1 in processes other than transcriptional regulation still remain undiscovered.…”
Section: Introductionmentioning
confidence: 99%
“…Although CARP-1/CCAR1 and DBC1 proteins are paralogs, a recent report revealed that both the DBC1 and CARP-1/CCAR1 are largely disordered proteins that evolved from a single common ancestor, the nematode Caenorhabditis elegans protein lateral signaling target (LST)-3 [24]. DBC1 emerged later in evolution than CARP-1/CCAR1 and first appeared in Danio rerio (zebrafish).…”
Section: Introductionmentioning
confidence: 99%
“…DBC1 emerged later in evolution than CARP-1/CCAR1 and first appeared in Danio rerio (zebrafish). Interestingly, the DBC1 gene is not present in insects, amphibians, or birds [24]. Nevertheless, a synergistic co-regulation of CARP-1/CCAR1 by DBC1 in mediating ERα target gene transcription in MCF7 and T47D HBC cells was noted in a recent study [25].…”
Section: Introductionmentioning
confidence: 99%